2021
DOI: 10.7717/peerj.11069
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale movements of common bottlenose dolphins in the Atlantic: dolphins with an international courtyard

Abstract: Wide-ranging connectivity patterns of common bottlenose dolphins (Tursiops truncatus) are generally poorly known worldwide and more so within the oceanic archipelagos of Macaronesia in the North East (NE) Atlantic. This study aimed to identify long-range movements between the archipelagos of Macaronesia that lie between 500 and 1,500 km apart, and between Madeira archipelago and the Portuguese continental shelf, through the compilation and comparison of bottlenose dolphin’s photo-identification catalogues from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…These movements are also in accordance with what is observed for other species in the same area (e.g. Steiner et al, 2015; Alves et al, 2019; Dinis et al, 2021). Studies on Bryde's whales have demonstrated movements of individuals between closer areas (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These movements are also in accordance with what is observed for other species in the same area (e.g. Steiner et al, 2015; Alves et al, 2019; Dinis et al, 2021). Studies on Bryde's whales have demonstrated movements of individuals between closer areas (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Connectivity between the Azores, Madeira, and the Canaries has been recorded for three species of cetaceans through photo-id Dinis et al, 2021). Additionally, the lack of genetic differentiation between populations in Macaronesia has been shown for: shortfinned pilot whales (Alves et al, 2013;Miralles et al, 2016); bottlenose dolphins (Quérouil et al, 2007); Atlantic spotted dolphins,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, baleen whales occur frequently in the archipelago, especially the Bryde's whale (Balaenoptera edeni), with a relatively high occurrence rate but with a very high interannual variation (Alves et al, 2018). Recent studies revealed cetacean interconnectivity among neighboring archipelagos, such as the Canaries and the Azores, with re-sightings of individuals from several species among the three archipelagos (e.g., Alves et al, 2019;Dinis et al, 2021). Additionally, Madeira constitutes an area of interest for several (at least ten) cetacean species due to being used for traveling, feeding, resting, socializing and calving (Alves et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One study registered the presence of six species along a ∼30 km coast stretch in the western Algarve during a little over 8 months (Castro, 2010), while the other study reported the presence of 11 species along the entire region during 6-month periods over 10 years (Laborde et al, 2019). Existing knowledge is mostly published as gray literature, while peer-reviewed publications are scarce and have focused on strandings (Silva and Sequeira, 2003;Sousa and Brito, 2012), aspects of population connectivity (Alves et al, 2019;Dinis et al, 2021) the population ecology of Delphinus delphis (Moura et al, 2012;Castro et al, 2020), and Orcinus orca (Esteban et al, 2013) description of opportunistic observations (Martin and Walker, 1997;Báez et al, 2007), interaction with fisheries (Goetz et al, 2015;Marçalo et al, 2015), diet (Marçalo et al, 2018(Marçalo et al, , 2021 or diet/trophic ecology (Giménez et al, 2017), behavioral responses to drones (Castro et al, 2021), and epidemiology (Bento et al, 2016).…”
Section: Introductionmentioning
confidence: 99%